KEPATUHAN HUKUM DALAM PERENCANAAN BISNIS USAHA KECIL MENENGAH (UKM) DI DESA BUNDER KEC. SUSUKAN KAB. CIREBON - Rohadi, Rohadi; Wahid, Abdul; Sumartini, Siti Sumartini (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
This study aims to find out how the obligations of the Cirebon Regency Education Office on the decision of the Cirebon Regency Regional Information Commission Number 002/VI/KIKC-PS-A/2018 on the completeness of public documents in Cirebon Regency. The form of the completeness of the requested public documents in the form of a request for a hardcopy / official copy of the 2017 Budget Implementation Document at the Cirebon Regency Education Office is open information based on the KIP Law. The obligation of the Cirebon Regency Education Office in accordance with its duties and functions as a Public Agency does not carry out the mandate of the KIP Law. The methodology used is a type of normative juridical research, namely legal research that places the law as a building system of norms. The system of norms in question is to recognize the principles, norms, rules of laws and regulations, court decisions, agreements and doctrines (teachings). Meanwhile, from the nature of the core research, it is included in the type of descriptive research in the form of diagnostic and evaluative by using qualitative exposure. The findings in this study, First; the weak response and no guarantees as well as the existence of deliberate institutional actions by the Cirebon Regency Education Office, so that the rights of applicants for public information are ignored so that they must take the public information dispute resolution route at the Cirebon Regency Regional Information Commission. Second; that the obligation of the Cirebon Regency Education Office is not to provide, not to provide and/or not to publish public information under its authority to applicants for public information until an unspecified time limit, so that unclear public information will appear and cause a problem. Keywords: Legal Compliance, Business Planning, SMEs, Warung Klontong.